A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil - Rocha, Pedro Carvalho; Sena, Letícia Moreira Ferraz De; Pezzuti, Tiago Leite; Leite, Felipe Sá Fortes; Svartman, Marta; Rosset, Sergio Daniel; Baldo, Diego; Garcia, Paulo Christiano De Anchietta (Zootaxa, 2017)
The Odontophrynus americanus species group is a complex of diploid and tetraploid species hardly distinguished by morphological characters. It currently consists of three allopatric diploid species (i.e. O. cordobae, O. lavillai, and O. maisuma) and one widely distributed tetraploid species (i.e. O. americanus). We herein describe a new diploid allopatric species from campo rupestre, a typical phytophysiognomy of the Espinhaço Range, Brazil. The new species is distinguishable by the diploid complement of 2n = 2x = 22 chromosomes, small to medium-sized dorsal dark brown blotches with low contrast on a light brown background, light mid-dorsal stripe absent or greatly interrupted in most specimens with yellowish coloration as the background of both head and flanks of the body, advertisement call with dominant frequency of 840–1080 Hz, pulse rate of 90.5–106.7 pulses/s, and small tadpoles (TL = 24.30–35.69 mm).